The role of materials in green buildings: identifying risks and barriers - Turan Karimaei; Faezeh Taherkhani; Shadi Motamedi (مهندسی و مدیریت ساخت, 2020)
The construction industry has a profound impact on the environment, the economy and public health. Public concerns about the impact of the construction industry on global climate change, energy consumption and public health, causes to researchers and executives focus on sustainable design and green building implementation. In order to properly design and implement a green building, it is necessary to identify the factors that may hinder the progress and even success of the project and to adopt an appropriate response to address these obstacles. The concept of green building is recently introduced in Iran, so this need is felt more than ever. Given that very limited executive experience of green buildings in Iran risks identification can be helpful to GB implementation. The aim of the present study is to identify the most important barriers and risks related to the green building materials sector. At first, using previous researches, risks and barriers were identified and then they were classified according to the stages of the project life cycle and the aspects of sustainability.